An analysis of Semantic changes of English lexical borrowings in Indonesia Tourism field - Tatu Siti Rohbiah (Loquen, 2020)
Abstract: This research was analyzed English lexical borrowings in the Indonesian tourism field. This research aims to classify and analyze the kinds of semantic changes that happen in the borrowed English tourism field in Indonesian. The method used was descriptive-qualitative content analysis to the corpus of data in the tourism field. The unit of analysis is the corpus of tourism fields collected from Indonesian magazines in June – July 2019, such as Intisari, tamasya, and Jalan – jalan. The result findings are 25 words meanings such as 12 words did not find changes of meaning and 13 words found changes of meaning of the tourism register in English adopted into Indonesian languages, such as extension, narrowing, degeneration, and regeneration. It means that Indonesian borrowed the foreign words, whose concept is adapted to the Indonesian. In Indonesian tourism field in semantic changes is adopted to the social condition.